Historiska narrativ och samtidens Sverige i teater för ung publik - Rebecca Brinch (Tidskrift för Litteraturvetenskap, 2023)
Historical Narratives and Contemporary Sweden in Theatre for Young Audiences. Eyewitnesses as Trauma-Drama.